Desenvolvimento de simuladores para treinamento em sintonia de controladores aplicados a equipamentos com grande risco de acidente - Cardoso Filho, Raul de Siqueira (2007)
The objective of this work is to develop real time dynamic simulators to use them as supporting tools in instrumentation and process control technical courses. The developed simulators are as following : - simulator for the equipment to test control valves showing all the acessories necessary to test a control valve. In this phase the concepts of Cv, curves inherent and installed of a control valve are introduced. - simulator in real time of a level control using P+I+D controller for a tank with the form of cylinder in the vertical position, in this phase the Ziegler-Nichols tunning methods are presented for systems with different response times and which are the influence of the control valve gain in the calculated tunning parameters. In this phase a system with fast response are presented. The same simulation is made using the same system with larger response time. During this simulation the influence of the gain of the valve is shown in the process response of the control and what is procedure to solve this problem. At this part, the advantages and disadvantages of the Ziegler-Nichols tunning methods in a practical applications. - simulator in real time of three elements level control for a boiler. In this phase a experimental method is showing for controller's tunning parameters. The experimental method presents advantages of practical order in reference of Ziegler- Nichols method. - This work was developed to permits to analyse the behaviour of dynamic system as well to study solutions that can do in the classroom without the concerns about safety which normally occurs in the industrial environment. The great target of this work is to show in the classroom experimental methods, as the own name indicates, only can be done in the real equipment. Also we believe that sigficant coast reduction can be achieve if simulators are used instead pilots plants.